2012
DOI: 10.1080/17290376.2012.665252
|View full text |Cite
|
Sign up to set email alerts
|

Patients-to-healthcare workers HIV transmission risk from sharp injuries, Southern Ethiopia

Abstract: Background: Accidental needlestick injury rate among healthcare workers in Hawassa is extremely high. Epidemiological findings proved the infectious potential of this injury contaminated with a Human Immunodeficiency Virus (HIV)-infected patient's blood.Objective: This study aimed at estimating the risk of HIV transmission from patients to healthcare workers in Hawassa City, Ethiopia.Method: A probabilistic risk model was employed. Scenario-based assumptions were made for the values of parameters following a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…[1,2] The worldwide incidence of percutaneous injury with a sharp object among the HCWs is estimated to be 3 million every year where a chance of four injuries per healthcare worker could occur annually [5,6]. Exposure to unsafe blood as a consequence of the injury may have a risk of infections to human immunodeficiency virus (HIV), hepatitis B (HBV), hepatitis C (HCV) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The worldwide incidence of percutaneous injury with a sharp object among the HCWs is estimated to be 3 million every year where a chance of four injuries per healthcare worker could occur annually [5,6]. Exposure to unsafe blood as a consequence of the injury may have a risk of infections to human immunodeficiency virus (HIV), hepatitis B (HBV), hepatitis C (HCV) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…2 Health-care workers (HCWs) are at risk of occupational acquisition of HIV infection, primarily due to accidental exposure to infected blood and bodily fluids. [3][4] The use of personal protective equipment (PPE), adherence to universal precautions, effective post-exposure management, engineered safer devices, injury surveillance, and relevant legislations are amongst strategies which are designed to maximise the safety of HCWs and patients in health-care setting. 5 The level of risk depends on the HIV prevalence of patients and the precautions the HCWs observe during a surgical, medical and clinical procedures while dealing with blood and bodily fluids.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Whilst studies indicate that the estimated risk of occupational HIV transmission in healthcare settings is low. 3,13 However, the risks of exposure and subsequent sero-conversion is high in high prevalence and resource limited settings especially if PEP strategies are inadequate. 3 Studies have indicated that the perception of risk of occupational HIV transmission amongst HCWs is high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such occupational injury leading to workers dissatisfaction and psychological trauma may reduce workers motivation and in turn may affect the quality of health care [13,15]. In our previous work we demonstrated the chance of occupational risk of contracting HIV from patient to healthcare workers in Hawassa City [16]. Owing to the considerable number of injuries in the study area [14] and the chance of cultural and ethnic influences; identification of health risk factors related to occupation is important for designing and employing effective risk preventive programs.…”
Section: Introductionmentioning
confidence: 99%